"Yvonne Rorke, Jim Rorke, Aunt Hilda and Patricia" - Rorke Family (1928)
Siblings Yvonne (Rorke) Pratt, James Ernest Rorke and Patricia (Rorke) Yorke, with their aunt, Hilda Samways (Forward) Pike, outside during the winter. James Rorke (1890-1947), son of James Addy Rorke and Mary (Wilcox) Rorke, was born 13 April 1890. He married Kathleen Forward, daughter of Ernest Edward Forward and Tryphena (Butt) Forward, on 23 May 1917, and had three children: Patricia (Rorke) Yorke, James Ernest Rorke and Yvonne (Rorke) Pratt. Patricia (Rorke) Yorke (1918- ) was born on 17 March 1918. She married Howard K. Yorke on 18 August 1945 and had a daughter, Lois Kathleen Yvonne. James Ernest Rorke (1919-2005) was born at Carbonear on 6 June 1919. He married Joy Elizabeth Newton of Maidenhead, Berks, England, and had two daughters: Joy Patricia, born on 24 March 1963 and Jill Yvonne, born on 18 January 1968. Yvonne (Rorke) Pratt (1922-1998) was born on 4 June 1922. Yvonne married Ewart A. Pratt (1919-2000), son of Calvert Coates Pratt and Agnes (Horwood) Pratt, on 30 October 1943 and had two children: Kathleen Agnes (Pratt) LeGrow and James Rorke Pratt (1949-2000). Yvonne died on 10 March 1998. Hilda Samways (Forward) Pike (1889-1982), the second of three daughters of Ernest Edward Forward and Tryphena (Butt) Forward, was born on 5 June 1889. Her sisters were Ernestine (Forward) Pike and Kathleen (Forward) Rorke. Her grandfather was Captain Mark William Forward. She married her sister Ernestine's former husband, Arthur S. Pike, on 5 June 1951, over a year after her sister died. Hilda died in 1982. The Rorke Family Photograph Collection contains 301 black and white and 28 colour photographs of the Rorke Family of Carbonear, Newfoundland, as well as the Forward and Bemister families from that area who are linked to it by marriage. Although spanning from the 1840s-1970s, most photos are from 1900-45, showing family events, homes and Newfoundland and Labrador locations. There is also an album of photos taken while James Rorke attended the Leys School in Cambridge, England.